Peran Inspektorat Dalam Melakukan Coaching dan Controlling SPIP Untuk Mempertahankan Hasil Opini Audit (Studi Pada Kantor Inspektorat Kabupaten Sumenep) - Dhea Ayu Risna; Aprilya Dwi Yandari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the role of the inspectorate in coaching and controlling SPIP in maintaining the results of the audit opinion. In this study, researchers also use qualitative research methods with an interpretive approach, in which the type of data used is documentary data based on inspection reports (LHP), Government Performance Accountability Reports (LAKIP), Review work papers (LHR), and other documents. Data collection techniques used in this study include interviews. The research respondents were inspectorate employees (IRBAN I, IRBAN IV, and IRBAN V) and one of the OPDs was a copyright employee of Sumenep Regency. The analysis technique used is descriptive qualitative. The results of this study indicate that the Sumenep Regency Inspectorate as a supporter in the administration of regional government in Sumenep Regency has been regulated and explained in the Sumenep Regency Regional Regulation Number 9 of 2016 and Regent's Regulation Number 21 of 2018. The role of the Sumenep Regency inspectorate in conducting Coaching and Controlling is carried out through five kinds forms, namely audits, reviews, evaluations, monitoring, and other supervisory activities.